2023
DOI: 10.1039/d2se01459a
|View full text |Cite
|
Sign up to set email alerts
|

A high-energy hybrid lithium-ion capacitor enabled by a mixed capacitive-battery storage LiFePO4 – AC cathode and a SnP2O7 – rGO anode

Abstract: In this work we present the development and optimization of a graphene-embedded Sn-based material and an activated carbon/lithium iron phosphate composite for a high-performing hybrid lithium-ion capacitor (LIC). For the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The AC in the composite delayed the overpotential of the LFP, improved the conductivity of the FP phase, and enhanced Li-ion transport at high current densities. Granados-Moreno et al [95] adopted a similar bifunctional blend of AC/LFP using a 60 wt.% AC and 40 wt.% LFP composite. This composite blend achieved a specific capacity of 102 mAh g −1 at 0.25 A g −1 and 80 mAh g −1 at 30 A g −1 .…”
Section: Bi-functional Hybrid Compositesmentioning
confidence: 99%
“…The AC in the composite delayed the overpotential of the LFP, improved the conductivity of the FP phase, and enhanced Li-ion transport at high current densities. Granados-Moreno et al [95] adopted a similar bifunctional blend of AC/LFP using a 60 wt.% AC and 40 wt.% LFP composite. This composite blend achieved a specific capacity of 102 mAh g −1 at 0.25 A g −1 and 80 mAh g −1 at 30 A g −1 .…”
Section: Bi-functional Hybrid Compositesmentioning
confidence: 99%
“…15,16 However, the alloying/dealloying process is accompanied by severe volume expansion, which leads to particle rupture and repeated formation/decomposition of the solid electrolyte interphase (SEI) film, thereby affecting electrochemical performance. 17,18 To solve these problems, several strategies for designing nanoscale materials (such as SNS nanosheets, 19 SnO 2 nanoparticles, 18 and SnO 2 quantum dots 17 SnS/polypyrrole ultrathin nanosheets 20 and graphene-tin oxide composites 21,22 ) have been explored in depth. In addition, the study of new anode material systems has confirmed that tinbased composite oxides are advanced anode materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, lithium-ion batteries (LIBs) are the preferred energy storage devices for portable devices and electric vehicles because of their high energy density. , Nevertheless, due to the insufficient and uneven geographical distribution of lithium resources, the cost of lithium continues to rise. Fortunately, sodium-ion batteries (SIBs) with similar energy storage mechanisms have lower costs, which fills in for large-scale energy storage systems. ,, However, the lithium storage capacity of commercial graphite anode electrodes is only 372 mA h g –1 , which hinders the practical application of LIBs in electric vehicles. Meanwhile, because the larger Na + radius increases the diffusion energy barrier, it is urgent to explore anode materials suitable for SIBs. ,, Alloy- or conversion-type anode materials are of great interest because of their high theoretical capacity. , Among them, tin-based materials have attracted much attention due to their low cost, high element abundance, and nontoxicity. The theoretical storage capacities of tin for lithium and sodium are 992 and 847 mA h g –1 , respectively. , However, the alloying/dealloying process is accompanied by severe volume expansion, which leads to particle rupture and repeated formation/decomposition of the solid electrolyte interphase (SEI) film, thereby affecting electrochemical performance. , To solve these problems, several strategies for designing nanoscale materials (such as SNS nanosheets, SnO 2 nanoparticles, and SnO 2 quantum dots) and constructing composites (such as polypyrrole/SnS/polypyrrole ultrathin nanosheets and graphene-tin oxide composites , ) have been explored in depth. In addition, the study of new anode material systems has confirmed that tin-based composite oxides are advanced anode materials. …”
Section: Introductionmentioning
confidence: 99%